Creating Legal Facts - Wina Khairina; Christian Lund (PCD Journal, 2020)
This paper examines how a local community has tried to legalise its possession of land in the outskirts of the city of Medan, Indonesia. In the absence of accessible legal pathways and in the face of state and gang violence, the community has resorted to an imaginative mimicry of legal land access procedures. This paper argues that law-making does not exclusively originate from the state, but also from society, and as such the community has effectively created legal facts. Data were collected through interviews and long-term contact with the community.